Cytokine Levels in Inner Ear Fluid of Young and Aged Mice as Molecular Biomarkers of Noise-Induced Hearing Loss - Landegger, Lukas D.; Vasilijic, Sasa; Fujita, Takeshi; Soares, Vitor Y.; Seist, Richard; Xu, Lei; Stankovic, Konstantina M. (Frontiers in Neurology, 2019)
Sensorineural hearing loss (SNHL) is the most common sensory deficit worldwide, frequently caused by noise trauma and aging, with inflammation being implicated in both pathologies. Here, we provide the first direct measurements of proinflammatory cytokines in inner ear fluid, perilymph, of adolescent and 2-year-old mice. The perilymph of adolescent mice exposed to the noise intensity resulting in permanent auditory threshold elevations had significantly increased levels of IL-6, TNF-α, and CXCL1 6 h after exposure, with CXCL1 levels being most elevated (19.3 ± 6.2 fold). We next provide the first immunohistochemical localization of CXCL1 in specific cochlear supporting cells, and its presumed receptor, Duffy antigen receptor for chemokines (DARC), in hair cells and spiral ganglion neurons. Our results demonstrate the feasibility of molecular diagnostics of SNHL using only 0.5 μL of perilymph, and motivate future sub-μL based diagnostics of human SNHL based on liquid biopsy of the inner ear to guide therapy, promote hearing protection, and monitor response to treatment.